Modern Greek Studies in Present-day Germany - Eideneier, Hans (Études helléniques / Hellenic Studies, 2006)
This article initially strives to correct claims about the existence of certain chairs of modern Greek studies around the world and the rosy image presented by “official Greece”. The author then focuses on Germany, where modern Greek studies face problems caused by changes not only in the German university but also within the broader new European and international context now less favourable. The author proposes a new start after the current crisis in modern Greek studies. He is not sure of a successful outcome but does not foresee failure either.